Exploring Self-Mention in The Yemeni EFL Argumentative Writing Across Three Proficiency Levels - Alward, Ali (Issues in Language Studies, 2019)
Self-mention used by university-level Yemeni writers is regarded as a challenging task. The overuse use of this feature is often considered as less formal and objective in academic writing. Despite the significance of this feature in academic writing, previous studies were mostly conducted in the Western cultural context. Research on self-mention produced by EFL learners of Arabic cultural background seems to be overlooked. Therefore, this study aimed to explore and compare the use of the first-person pronouns across three proficiency levels in an argumentative paragraph written by 80 third-year undergraduate students. Data were collected, assessed by ELT specialists, and then quantitatively analyzed. The results revealed that Yemeni EFL learners make extensive use of the first-person pronouns in their argumentative paragraphs. Differences were found in the occurrences of the first-person pronouns across three proficiency levels. The results also indicated that learners with a high proficiency level tend to use the first-person pronouns less than learners at low and intermediate proficiency levels. Since low-proficient learners rely more on the use of the first-person pronouns than those at higher levels, learners need to be exposed to a variety of strategies of how they can project their voice appropriately in their written texts.